(untitled) (REMUNOM, 2023)
There is no doubt that the internet theme is extremely current in the context in which we live, since, through the Internet, it is possible to shop, watch movies and series, have access to bank accounts, among other infinite navigation possibilities created for make life easier for individuals. It happens that users are faced with the message of accepting or rejecting cookies on most sites, and it is often mandatory to accept such a policy of use. Thus, this article aims to analyze the functioning of the use of cookies by websites. The purpose of this article is to explain what these files are, their functionality and how they are used on websites, in addition to analyzing whether cookies can collect sensitive data from users, so that this can affect personality rights. As objects for the construction of this article, books and articles already published on the subject will be used. In addition, this research also aims to explain the functioning of the cookie use policy by websites under the protection of the Civil Rights Framework for the Internet (Law nº 12.965/2014) and the General Data Protection Law (Law nº 13.709/ 2018), in order to verify which data is collected by the websites’ cookies, in addition to analyzing whether such data collected is personal and sensitive so that it may or may not affect the personality rights of users.